Pengaruh Project Based Learning Terhadap Keterampilan Abad 21 Pada Siswa Kelas XI TITL SMKN 1 Jakarta - Anissa Nurul Pratiwi; Atep Iman; Irwanto (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the effect of implementing the PjBL model on the 21st-century skills of 11th-grade TITL students at SMKN 1 Jakarta in the subject of Electrical Lighting Installation. The study was conducted at SMKN 1 Jakarta during the 2025–2026 academic year using a quasi-experimental design, specifically a nonequivalent control group design. The study population consisted of 101 11th-grade TITL students, with a saturated purposive sampling technique resulting in two classes: 11th-grade TITL 2 (33 students) as the experimental group 1 and 11th-grade TITL 1 (33 students) as the control group. Based on the results of the study, it can be concluded that the implementation of the PjBL model has a significant effect on improving students’ 21st-century skills (4Cs), which include critical thinking, creativity, collaboration, and communication. This is indicated by a higher average score in the experimental class compared to the control class, where the experimental class showed an increase of 13.46 points, while the control class only increased by 8.03 points. Furthermore, the results of the hypothesis test using an independent samples t-test showed a significance value (two-tailed) of 0.027 (< 0.05), leading to the rejection of H₀ and the acceptance of Ha.